THE EXISTENCE OF BASYARNAS IN THE JUSTICE SYSTEM IN INDONESIA - Sahrudi, Sahrudi; Syahrul Ansari, Teuku; Koswara, Indra; Hadipura, Margo (Universitas Ekasakti, 2023)
In legal matters, there are two attempts to resolve disputes between parties, one of which is by using a sharia-based dispute resolution system. Settlement of sharia-based disputes includes non-litigation (outside court) and/or litigation in court). Sharia disputes in court (Litigation) are requested through religious courts, and dispute resolution outside the court (Non Litigation) through sharia Arbitration bodies. In Indonesia, the institution that resolves sharia arbitration disputes is called BASYARNAS (National Sharia Arbitration Board), and the procedures for settlement are not much different from arbitration procedures in general. The legal basis for the settlement of sharia arbitration disputes is regulated in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and furthermore regarding the execution of sharia arbitral awards is regulated in Supreme Court Circular Letter No. 08 of 2008. This research uses a qualitative method with a normative approach and uses a library research collection method, as well as analyzing documents, data, information related to BASYARNAS. The results of research on the existence of BASYARNAS still depend on the district court.